The Correlation between Vocabulary Mastery and Speaking Skills of Female Boarding Students at Islamic High School - Rahita Rahmadya Waluyo; Muhammad Taufiq (Lingua Franca, 2026)
This study determines the relationship between vocabulary mastery (mufrodat) and speaking skills (maharah kalam) among female boarding students. Employing a quantitative correlational design, the total sampling technique was used to select all 32 tenth-grade female boarding students at MAN 2 Model Medan. Data were collected using valid and reliable vocabulary and speaking tests and analyzed using descriptive statistics and Pearson Product-Moment correlation tests in SPSS, along with tests of normality and linearity. Results showed 50% of students had moderate vocabulary mastery, and 71.88% fell into the moderate speaking category. The Pearson correlation yielded a coefficient () of 0.124 with a significance value of 0.501. Since , no significant relationship exists between vocabulary mastery and speaking skills within this population. Theoretically, this study offers an empirical critique of Arabic pedagogy by demonstrating a clear decoupling between lexical competence and communicative performance in high-control language environments. In practice, these findings shift the focus of boarding school language strategies from passive vocabulary accumulation (input) to mitigating psychological barriers, such as language anxiety, and maximizing active speech production (output) in daily communication.